Compressive-tensile fatigue behavior of cords/rubber composites - Tonatto, Maikson L.P.; Forte, Maria M.C.; Amico, Sandro C. (Polymer testing, 2017)
Cord/rubber composites are used to build complex structures which may be submitted to cyclic loads, sometimes leading to critical fatigue failure. The focus of this study is to investigate the cyclic compressive/tensile strain behavior of polyester, polyamide and hybrid polyaramid/polyamide cords. For that, the cords were embedded in rubber belts to be used in a specially designed rotating pulley equipment that allows monitoring and controlling of tensile force, frequency and strain level. All fatigue tests were performed using stress-control mode, and tensile residual strength of the cords was measured as a function of material type, number of cycles and compressive/tensile strain level. The results show that compressive and tensile cyclic strains decrease residual properties. Hybrid cords showed higher residual strength than polyester and polyamide cords when subject to high compressive strain or high number of cycles. Moreover, morphological evaluation indicated failure to be associated with microbuckling and extensive fibrillation.